GAMBARAN PRAKTEK IBADAH SHOLAT PASIEN YANG DIRAWAT DIRUMAH SAKIT X - Kadun, Murtiningsih; Zaly, Nedra Wati (Universitas Islam Negeri Alauddin Makassar, 2020)
Prayer is an obligation for every Muslim from baligh to the end of life. Patients who are admitted to the Hospital there are Rukhshah (ease of doing worship). If the patient is unable to stand up, then prayer can be done by sitting, lying down or by gesturing. This study aims to get an overview of the prayer practice of patients being admitted to the hospital and the reasons for the patients not praying while being admitted to the hospital. The sample of this study was 65 patients admitted to the Hospital X that were collected by Jayakarta STIKes Students when conducting spiritual studies patients to do nursing care when practicing nurses basic nursing profession in the Academic Year 2019/2020. The questionnaire includes a spiritual assessment contained in the portfolio. The research method is cross sectional study with descriptive studies. The results showed the majority of patients (41.5%, N=65) during their admitted to the hospital had never prayed. The reason for patients not praying while being admitted to the Hospital the majority (23.1%) is because they do not know how to pray, before being sick they rarely pray (18.5%), some (9.2%) argue that if there is no need to pray, there is no prayer equipment (4.6) %). Recommendations for further research are research on nurses' knowledge about prayer for patients admitted to the hospitals. Furthermore, nurses need to be given training on the practice of prayer and rukhshah to worship for patients admitted to the hospitals. Keywords: Prayer practice, patients, admitted to the Hospital.